2021
DOI: 10.3399/bjgp.2020.1093
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of oral ondansetron for children with acute gastroenteritis in primary care: a randomised controlled trial

Abstract: Background: Acute gastroenteritis is a common childhood disease with substantial medical and indirect costs, mostly because of referral, hospitalization and parental absence from work. Aim: To determine the cost-effectiveness of adding oral ondansetron to care-as-usual for children with acute gastroenteritis in out-of-hours primary care. Design and setting: A pragmatic randomised controlled trial at three out-of-hours primary care centres, with a follow-up of 7 days. Method: Inclusion criteria were: 1) age 6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In the Netherlands, the recommended single dose of oral ondansetron is 0.1 mg/kg, while Australia advises a higher single dosage regimen [8-15kg 2mg; 15-30kg 4mg; >30kg 6-8mg] [ 19 , 28 ] consistent with previous research [ 29 , 30 ]. The lower dosage strategy in the Netherlands is based on a more recent randomized controlled trial that found [cost-]effectiveness at a lower dosage [ 31 , 32 ]. Furthermore, another study has revealed that children with acute gastroenteritis who received higher doses of ondansetron did not experience a greater reduction in vomiting, nor did they require less intravenous rehydration or hospitalizations compared to children who received lower doses [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the Netherlands, the recommended single dose of oral ondansetron is 0.1 mg/kg, while Australia advises a higher single dosage regimen [8-15kg 2mg; 15-30kg 4mg; >30kg 6-8mg] [ 19 , 28 ] consistent with previous research [ 29 , 30 ]. The lower dosage strategy in the Netherlands is based on a more recent randomized controlled trial that found [cost-]effectiveness at a lower dosage [ 31 , 32 ]. Furthermore, another study has revealed that children with acute gastroenteritis who received higher doses of ondansetron did not experience a greater reduction in vomiting, nor did they require less intravenous rehydration or hospitalizations compared to children who received lower doses [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of different routes of ondansetron administration in children having nausea and vomiting has been studied previously, and it was found that orally disintegrated ondansetron tablet provides an easy and acceptable route of administration. It is non-invasive compared to intravenous ondansetron and hence preferred, especially in children who are eligible to be managed as an out-patient [20] . Our study also shows that orally disintegrated ondansetron is accepted well by children having symptoms of acute gastroenteritis.…”
Section: Discussionmentioning
confidence: 99%
“…17 As Ondansetron is believed to reduce emesis, it might be directly improving or the oral intake of ORT which further goes on to reduce the need for IV rehydration as well as hospitalization. [18][19][20] The strengths of this study include, being the 1 st study from a resource limited setting of Pakistan comparing efficacy of Domperidone versus…”
Section: Discussionmentioning
confidence: 99%